PENGEMBANGAN MODEL INTEGRATIF BAHAN AJAR BAHASA INDONESIA RANAH SOSIAL BUDAYA BERBASIS ICT BAGI PENUTUR ASING TINGKAT MENENGAH - Muhammad Badrus Siroj (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
This paper is aiming at developing an integrative model of Indonesian language for foreigners (BIPA) teaching material for non native speakers (NNS).Â  This research is a research and development based on Borg and Gall concept that has been modified by Sukmadinata. The findings generated in this research are a guide of ICT based integrative model development of social cultural BIPA teaching material that is arranged (1) based on integrative approach, (2) developed in socio cultural domain, (3) oriented in communicative ability improvement, and (4) elaborated in ICT utilization basis.Â  Based on the result of the product trials, it is revealed that there is improvement in the average score of learnersâ€™ communicative ability, namely 57 to 75. Thus, ICT based integrative model of social cultural BIPA teaching material in this middle level is able to improve foreign learnersâ€™ speaking fluency. Learners proficiency level which initially was in level 2+ with theÂ  description â€œable to fill the social routine needs to work necessity finitelyâ€ changed to level 3+ with a description that leads to â€œable to speak with grammar and vocabulary accuracy to participate in formal and non formal conversation on the practical, social, and professional problemsâ€. Suggestions obtained here is that the findings of this research can be used to teach BIPA in Indonesia. However, further researches is needed